EVALUATING DETERMINANTS OF PROPERTY TAX REASSESSMENT: MALAYSIAN PRACTITIONERS’ PRELIMINARY OBSERVATIONS - Senawi, Asma; Osmadi, Atasya; Abd Rahman, Nor Azalina Yusnita (PLANNING MALAYSIA, 2022)
Property tax plays an essential role in funding local government overheads to provide basic services for residents. However, too little research has stressed the importance of property tax assessment quality, especially in terms of reassessment. The absence of a regular and frequent reassessment process leads to distortions in tax payments, lower revenue generation, and a higher risk of significant increases in tax liability. A preliminary survey was conducted to unpack the determinants of property tax reassessment to address this issue. Survey data from 37 officers revealed that nine of the identified determinants have a significant and positive impact on the successful implementation of property tax reassessment in Malaysia, with staff capacity an essential aspect. The neighbouring municipality influence appears to play a less impactful role. These findings highlight the success factors in conducting property tax reassessment activity, which would assist the long-term success of local authorities. Despite the importance of property tax implementation for the local authorities, this research suggests that organisations should also ensure the quality of property tax and its frequent reassessment to enhance overall performance.